2019
DOI: 10.1136/bmjopen-2018-025166
|View full text |Cite
|
Sign up to set email alerts
|

Patient, client, consumer, survivor or other alternatives? A scoping review of preferred terms for labelling individuals who access healthcare across settings

Abstract: ObjectivesUse of the term ‘patient’ has been recently debated, compared with alternatives including ‘consumer’ and ‘client’. This scoping study aimed to provide an integrated view of preferred labels across healthcare contexts and countries to clarify labelling preferences of individuals accessing healthcare.DesignScoping study.Data sourcesA preliminary literature search using GoogleScholar, Medline, Embase and PsycINFO found 43 key papers discussing terminology for labelling individuals accessing healthcare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 79 publications
1
55
1
1
Order By: Relevance
“…4,5 Many surveys have indeed shown an overwhelming majority preferring to be addressed as patients. 6…”
Section: The Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Many surveys have indeed shown an overwhelming majority preferring to be addressed as patients. 6…”
Section: The Patientmentioning
confidence: 99%
“…Refer to people with a mental illness as ‘patients’ (in keeping with the rest of medicine) since research has found that the vast majority favour this designation over consumer, client or user. 6…”
Section: The Psychiatristmentioning
confidence: 99%
“…How the term "survivor" is understood by patients may affect their quality of life and the care they are comfortable receiving. Endorsing the label or accepting the identity "survivor" has been associated with greater positive mood, satisfaction with life, and higher self-care [2,3]. However, not all people diagnosed with cancer are comfortable adopting the "survivor" label.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Debate about appropriate nomenclature (‘patients’, ‘clients’, ‘service users’) for people who access healthcare continues ( Costa, Mercieca-Bebber, Tesson, Seidler, & Lopez, 2019 ). Here, we use these terms interchangeably.…”
mentioning
confidence: 99%